Multisensory Audiovisual Processing in Children With a Sensory Processing Disorder (II): Speech Integration Under Noisy Environmental Conditions - Foxe, John J.; Del Bene, Victor A.; Ross, Lars A.; Ridgway, Elizabeth M.; Francisco, Ana A.; Molholm, Sophie (Frontiers in Integrative Neuroscience, 2020)
Background: There exists a cohort of children and adults who exhibit an inordinately high degree of discomfort when experiencing what would be considered moderate and manageable levels of sensory input. That is, they show over-responsivity in the face of entirely typical sound, light, touch, taste or smell inputs, and this occurs to such an extent that it interferes with their daily functioning and reaches clinical levels of dysfunction. What marks these individuals apart is that this sensory processing disorder (SPD) is observed in the absence of other symptom clusters that would result in a diagnosis of Autism, ADHD, or other neurodevelopmental disorder more typically associated with sensory processing difficulties. One major theory forwarded to account for these sensory processing disorders posits a deficit in multisensory integration, such that the various sensory inputs are not appropriately integrated in the central nervous system, leading to an overwhelming sensory-perceptual environment, and in turn to the sensory-defensive phenotype observed in these individuals. Methods: We tested whether children (6-16 years) with an over-responsive SPD phenotype (N=12) integrated multisensory speech differently from age-matched typically-developing controls (TD: N=12). Participants identified monosyllabic words while background noise level and sensory modality (auditory-alone, visual-alone, audio-visual) were varied in pseudorandom order. Improved word identification when speech was both seen and heard compared to when it was simply heard served to index multisensory speech integration. Results: School-aged children with an SPD show a deficit in the ability to benefit from the combination of both seen and heard speech inputs under noisy environmental conditions, suggesting that these children do not benefit from multisensory integrative processing to the same extent as their typically developing peers. In contrast, auditory-alone performance did not differ between the groups, signifying that this multisensory deficit is not simply due to impaired processing of auditory speech. Conclusions: Children with an over-responsive SPD show substantial reduction in their ability to benefit from complementary audio-visual speech, to enhance speech perception in a noisy environment. This has clear implications for performance in the class room and other learning environments. Impaired multisensory integration may contribute to sensory over-reactivity that is definitional of SPD.